PERENCANAAN PERMUKIMAN NELAYAN DI PANTAI TIMUR SURABAYA - Ratna Darmiwati; Ida Bagus Gede Primayatna; Ketut Muliawan S.; Wayan Nada; Dw. Nym. Wastika (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2001)
At Kalisari's area planning strategic, is necessary to be complecationed the elements as follows